KORELASI LAMA MENDERITA HIPERTENSI DENGAN STADIUM KATARAK SENILIS DI RUMAH SAKIT KHUSUS MATA (RSKM) REGINA EYE CENTER PADANG - Salsabila Fauzia; Rosmaini, Rosmaini; Zukhri Zainun (Nusantara Hasana Journal, 2025)
Cataract is an eye disease characterized by clouding of the lens. Cataracts that develop after the age of 60 are referred to as senile cataracts, a leading cause of blindness among the elderly, marked by progressive lens opacification. Hypertension is one of the risk factors, where cataracts may develop through mechanisms involving increased oxidative stress. This research to analyze the correlation between the duration of hypertension and the stage of senile cataracts. This study falls under ophthalmology and internal medicine. It used a quantitative analytical method with a cross-sectional design. Primary and secondary data were collected from senile cataract patients. A total of 35 patients were selected using purposive sampling, based on inclusion and exclusion criteria. Most patients were in the young elderly group (60–69 years; 71.4%), female (65.7%), and housewives (60%). The majority had hypertension for ≤5 years (62.9%) and were diagnosed with immature cataracts (71.4%). A Spearman correlation test showed a significant correlation (p = 0.01; r = +0.561) between the duration of hypertension and cataract stage. The longer the patient had hypertension, the more advanced the cataract stage. There is a significant correlation between the duration of hypertension and the stage of senile cataracts.